2011
DOI: 10.1055/s-0031-1280224
|View full text |Cite
|
Sign up to set email alerts
|

Keratokonus: Klinik, Diagnostik, Therapiemöglichkeiten

Abstract: Geschützte Warennamen (Warenzeichen) werden nicht besonders kenntlich gemacht. Aus dem Fehlen eines solchen Hinweises kann also nicht geschlossen werden, dass es sich um einen freien Warennamen handelt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
0
2
0
3
Order By: Relevance
“…For example, associations with genetic disorders like Down’s syndrome [ 4 ] and influences of atopic dermatitis and eye rubbing have been described [ 5 ]. Keratoconus usually starts during adolescence and progresses until the third or fourth decade of life [ 6 , 7 ]. The CLEK (Collaborative Longitudinal Evaluation of Keratoconus) Study [ 8 ] showed a mean change in flatter keratometry readings of 1.6 dioptres in the natural course of keratoconus progression over an eight year period, where higher rates of progression occurred in younger than in older patients.…”
Section: Introductionmentioning
confidence: 99%
“…For example, associations with genetic disorders like Down’s syndrome [ 4 ] and influences of atopic dermatitis and eye rubbing have been described [ 5 ]. Keratoconus usually starts during adolescence and progresses until the third or fourth decade of life [ 6 , 7 ]. The CLEK (Collaborative Longitudinal Evaluation of Keratoconus) Study [ 8 ] showed a mean change in flatter keratometry readings of 1.6 dioptres in the natural course of keratoconus progression over an eight year period, where higher rates of progression occurred in younger than in older patients.…”
Section: Introductionmentioning
confidence: 99%
“…In präoperativen Kontrollen können ektatische Veränderungen der Hornhaut anhand von topografischen Mustern dargestellt werden. Eine für den Keratokonus typische Form wäre eine zentralisierte Sanduhrfigur mit abgeknickten Achsen [7]. Im Verlauf postoperativer Kontrollen können iatrogene Keratektasien diagnostiziert werden [8].…”
Section: Comparison Of Discriminant Analysis and Decision Trees For Tunclassified
“…Vision-specific quality of life is significantly affected by keratoconus [ 3 ]. In most cases the disease is bilateral and mostly diagnosed in the second or third decade of life with an incidence of 55 : 100,000 [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%